Flared textile cuff to be apposed on the proximal sealing zone in fenestrated stent-grafts. Issue 3 (February 2014) - Wang, Fujun; Li, Chaojing; Wang, Lu; Li, Cong; Li, Yuling; Lin, Jing; Jing, Zaiping; Douglas, Graeham; Nutley, Mark; Guidoin, Robert
Current customized fenestrated devices require a fabrication delay of 4–6 weeks and therefore cannot be considered for the treatment of emergent or urgent aortic pathology. A flared textile cuff capable of better sealing the connection between a stent-graft fenestration and a branching stent-graft could bring more flexibility in treating patients with peri- and juxta-renal abdominal aortic aneurysms. Four different flared textile cuff prototypes were fabricated by compression molding of woven fabrics having structure similar to those of commercially available devices. Each cuff comprised a flat collar as a base, an arc as a curved section, and a top as a regular fabric tube. The fabric count, density, and thickness decreased from the first to the third sections and the results differed according to the structure. The physical and mechanical properties of these flared fabric cuffs were similar to those found in commercially available stent-grafts. The flared textile cuffs showed a scope of properties adapted for easier delivery and are acceptable to various sizes and shapes of fenestration. The development of flared textile cuffs represents a considerable advancement in endovascular therapy: (1) allowing a fenestrated solution to be readily available off-the-shelf; (2) providing an adequate seal of the ancillary stent-graft to the main body of the stent-graft.